From utility demand side management to low-carbon transitions: Opportunities and challenges for energy efficiency governance in a new era. (January 2020) - Haley, Brendan; Gaede, James; Winfield, Mark; Love, Peter
Abstract: Demand side management (DSM) programs operating within utility systems have played an important role in energy efficiency program delivery. In recent years, utility DSM institutions have been challenged to consider the implications of low-carbon transitions and the wider benefits of energy efficiency. In this perspectives paper we trace the historical evolution from utility DSM frameworks primarily focused on economic efficiency objectives towards consideration of the larger transitions in energy demand required to create a low-carbon society. We highlight the opportunities a low-carbon transition agenda creates to deliver more comprehensive energy efficiency strategies, as well as strengths of the utility DSM framework that new low-carbon institutions might be challenged to emulate. We conclude by calling for a new research program on institutional design to promote sustainable energy demand in a low-carbon transitions era.